Education, Science Education and Pedagogy - Valencia Salazar, Edilberto (2015)
An approach on Education, Science Education and Pedagogy was performed by analysis of definitions, objectives, rationale, their scientific attribute and their interrelationships. It was concluded that education is not a science, but a process leading to each person: to find, to promote and growing among others, their creative potential, and this is achieved if the human being: learning to know, learning to do, learn to live and learn to be. There is no science itself of Education but it is based on theories of other sciences. What does exist is sciences underlying, explain and been apply in Education. Pedagogy is part of the construct of Education, is immersed linking theory with another to translate the goals of Education in humans. Also, it was shown that pedagogy is not a science, and the definition that best fits is redefining the art of teaching.